IMPLEMENTASI PROGRAM PENDAFTARAN TANAH SISTEMATIS LENGKAP (PTSL) DI KABUPATEN KUANTAN SINGINGI TAHUN 2017 - Alfi Khairi; Raja Muhammad Amin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
PTSL is a land registration activity which includes the collection and determination of the truth of physical data and juridical data concerning one or several objects of land registration for the purposes of registration, the costs of which are not burdened to the public. The formulation of the problem of this study is: How is the implementation of the Complete Systematic Land Registration Program (PTSL) in Kuantan Singingi Regency in 2017?This research is a descriptive research with a qualitative approach. The location of this study was conducted in Kuantan Singingi Regency. Data collection techniques are carried out with qualitative data analysis. While the results of the study concluded that the Implementation of the Complete Systematic Land Registration Program (PTSL) in Kuantan Singingi Regency in 2017 was not good enough. This is the most dominant thing to influence the Implementation of the Complete Systematic Land Registration Program (PTSL) in Kuantan Singingi Regency is a resource factor. The implementation of the Complete Systematic Land Registration Program (PTSL) in Kuantan Singingi Regency in 2017 does not reach the target or volume that has been planned, especially staff totaling 6 (six) staffs are not balanced with the number of targets that have been set in the Complete Systematic Land Registration Program (PTSL ) in Kuantan Singingi Regency.Keywords: Implementation, Complete Systematic Land Registration Program (PTSL )